Features of diagnostics of gastroesophageal and duodenogastric reflux in patients with complicated forms of peptic ulcer. - N. N. Veligotskii; V. V. Komarchuk; E. V. Komarchuk; I. V. Teslenko; A. S. Chebotaryov (Medičnì Perspektivi, 2018)
Purpose – to improve the results of surgical treatment of duodenal ulcer due to preoperative diagnosis of concomitant reflux disease and its correction. Before surgery, 46 patients with complicated forms of peptic  ulcer disease underwent pH monitoring and 23 – impedance-pH monitoring. Pathological gastroesophageal reflux was found in 58 cases. Before surgery, esophageal pH monitoring was performed in 46 patients with complicated forms of peptic ulcer disease. Against the background of hyper – and normacidity of the stomach in 39 patients pathological acidic gastroesophageal reflux disease with a significant increase of De Meester index was confirmed. Impedance-pH monitoring was performed before surgery in 23 patients with complicated forms of peptic ulcer and concomitant gastroesophageal reflux. Erosive form of gastroesophageal reflux disease was confirmed endoscopically in all patients with hyperacidity (17) and normal acidity (6) of the stomach. In 19 cases pathological gastroesophageal reflux disease was found. In 13 cases the cause of disorders in anti-reflux barrier was a diaphragmatic hernia of I-II degree. Gastroesophageal reflux disease was caused by increased intragastric pressure due to ulcer stenosis in 6 patients. pH- monitoring in patients with acidic gastroesophageal reflux allows to establish a pathological or physiological reflux. Conducting impedance-pH monitoring allows to determine the number of reflux episodes and their qualitative characteristics (acidic or alkaline; liquid, gas or mixed), as well as to determine the indications for a differentiated approach in the treatment of gastroesophageal reflux.